Towards a harmonized European surveillance for dietary and physical activity indicators in young and adult populations - Hebestreit, Antje; Do, Stefanie; Wolters, Maike; Mensink, Gert B.M.; Garnica-Rosas, Lina; Abu-Omar, Karim; Messing, Sven; Neumann-Podczaska, Agnieszka; Wieczorowska-Tobis, Katarzyna; Lien, Nanna; Stanley, Isobel; Ahrens, Wolfgang; et al. (European Journal of Public Health, 2022)
Background The Policy Evaluation Network proposes a consolidated approach to measure comparable health indicators across European health surveillance systems to evaluate effectiveness of policy action. Methods In a stepwise approach, questionnaire items used by the systems for measuring diet and physical activity data to describe health indicators were identified based on their validity, reliability, and suitability to monitor achievement of health recommendations. They were collated to unified questionnaire modules and discussed bilaterally with representatives of these systems to explore barriers and facilitators for implementation. Also, establishment of a methodological competence platform was proposed, in which the surveillance and monitoring systems agree on the priorities and common quality standards for the harmonization process and to coordinate the integration of questionnaire modules into existing systems. Results In total, seven questionnaire modules were developed, of which two diet and two physical activity modules were proposed for implementation. Each module allows measurement of data reflecting only partial aspects of national and WHO recommendations related to diet and physical activity. Main barriers were the requirements of systems to monitor temporal trends and to minimize costs. Main facilitator for implementation was the systems’ use of questionnaire items that were comparable to the unified modules. Representatives agreed to participate in a methodological competence platform. Conclusion We successfully took first steps in the realization of the roadmap towards a harmonization of European surveillance by introducing unified questionnaire modules allowing the collection of comparable health indicators and by initiating the establishment of a competence platform to guide this process.<br